A model for gamma-ray sources in the galactic halo - Vila, Gabriela Soledad (2007)
Among the galactic gamma-ray sources detected by the EGRET instrument there exists a group located at high galactic latitudes, distributed as a halo around the galactic centre. These sources are X-ray quiet with soft spectra at gamma-rays. Their variability on short timescales indicates the presence of a compact object. In this work we present a model for gamma-ray halo sources based on hadronic processes in the jet of a low-mass microquasar. Several interaction mechanisms between relativistic protons and local fields are taken into account. We also estimate the contribution to the spectrum of primary leptons. Finally, we compare our results with the general properties of the halo gamma-ray sources and make some predictions for the forthcoming satellite-borne gamma-ray telescopes.